Minat Berwirausaha Mahasiswa Perempuan Ditinjau dari Literasi Digital, Pendidikan Kewirausahaan dan Efikasi Diri - Rosalia Viani Eci; Jacob Abolla Daka; Fernando Saragih (Varied Knowledge Journal, 2026)
This study was motivated by the low entrepreneurial interest among female students at Nusa Cendana University due to low self-confidence, limited entrepreneurial competence, conventional mindsets, and restricted access to capital. The study aims to analyze the influence of digital literacy and entrepreneurship education on entrepreneurial interest, with self-efficacy serving as a mediating variable. This research employed a quantitative explanatory approach with a sample of 110 respondents selected through accidental sampling. Data were collected using a likert-scale questionnaire and analyzed using path analysis. The results showed that digital literacy and entrepreneurship education had a positive and significant effect on entrepreneurial interest, while self-efficacy was able to mediate the relationship. The coefficient of determination value of 44.3% indicates that entrepreneurial interest was influenced by the variables examined in this study, while the remaining percentage was affected by other factors outside the model. Theoretically, this study enriches the Theory of Planned Behavior (TPB) through the role of self-efficacy as a mediating variable. Practically, the findings provide implications for universities in designing entrepreneurship learning that can strengthen students’ self-confidence to encourage entrepreneurial interest.